Ruqyah Syar'iyyah sebagai Terapi Alternatif dalam Psikologi Islam: Kontroversi dan Perkembangan - Rahmani, Fathiya; Aziz, Alif Ikhwani (Institut Agama Islam Negeri Parepare, 2024)
This article explores the effectiveness of ruqyah syar'iyyah therapy in improving the mental well-being of patients through a quantitative approach. The method used is a pre-test and post-test survey involving 25 patients undergoing ruqyah syar'iyyah therapy. The research design is descriptive and analytical, with data collected by measuring anxiety scores before and after therapy, as well as through interviews with patients and practitioners. The results show a significant decrease in the average anxiety score from 78 to 51 after therapy. Additionally, 70% of patients reported mood improvement and stress reduction. Interviews with practitioners also confirmed significant improvements in patients' emotional conditions, with 80% of patients feeling more satisfied with this therapy compared to other methods. The average increase in emotional well-being scores of 25% indicates that ruqyah syar'iyyah therapy is not only effective in reducing anxiety but also has a positive impact on overall emotional well-being. These findings support the potential of this therapy as an alternative in psychological practice for addressing mental health issues.